Más Allá del Diagnóstico: Marco Multidimensional de Fenotipos Clínicos y Biológicos en los Trastornos del Neurodesarrollo para una Intervención de Precisión - Juan José Vergara Serpa; Candelaria Rosa Villadiego Verbel (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
Introduction: Neurodevelopmental disorders are characterized by substantial clinical and biological heterogeneity. Individuals with the same diagnosis may differ in cognitive functioning, sensory regulation, motor performance, sleep, gastrointestinal health, and other clinically relevant dimensions. Although categorical models are essential for diagnosis, they may be insufficient on their own to guide comprehensive assessment and individualized intervention. Objective: To propose a multidimensional framework for organizing the principal clinical and biological phenotypes described in neurodevelopmental disorders and to examine its potential utility for precision medicine, nutrition, and neurorehabilitation. Methods: A critical narrative review was conducted using a structured search of the biomedical literature addressing phenotypic heterogeneity, dimensional models, co-occurring conditions, and clinical or biological mechanisms associated with neurodevelopmental disorders. Evidence was organized through a conceptual synthesis aimed at identifying transdiagnostic domains, interactions, clinical applications, and limitations. Reporting quality was guided by SANRA, and the electronic search strategy underwent an independent PRESS-based review. Results: The Multidimensional Framework of Phenotypes in Neurodevelopmental Disorders (MFP‑NDD) was formulated. It comprises eight domains: neurocognitive and executive; sensory and self-regulatory; neuroimmune and inflammatory; autonomic; gastrointestinal–microbiota–gut–brain; metabolic, nutritional, and mitochondrial; motor, neuromuscular, and praxis-related; and sleep and circadian regulation. These domains are conceptualized as coexisting, dynamic, and non-mutually exclusive dimensions. The framework distinguishes reported manifestations, documented findings, confirmed conditions, biomarkers, and demonstrated mechanisms. Conclusions: The MFP‑NDD may complement categorical diagnosis, support interdisciplinary coordination, and contribute to the future development of precision interventions. It is neither a diagnostic classification nor a validated clinical instrument. Clinical application will require studies of consensus, feasibility, validity, reliability, longitudinal stability, and clinical utility.